MEMETAKAN KONFLIK DALAM PENGADAAN TANAH BANDARA KOMODO - Mr Padjo; M. Nazir Salim (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
The research is aimed at describing conflict on the land acquisition of expanding the Komodo Airport at WestManggarai Regency, NTT. The expansion of airport is intended to accommodate the tourist since Komodo was determined to beThe New 7 Wonder of Nature. The increase of tourist place, especially on Sail Komodo program in September 2013. The focus ofexpansion was on three places namely the 300 meter runaway which belonged to Department of Transportation. The west part ofthe airport that is Binongko Hill and Batu Hill. At the last two areas, the expansion was done by eliminating the people’s land. Thisresulted protests from the society as they do not get any financial return. Using the qualitative and critical approaches, the studywas able to show the map of conflict location between the regional government and the society. At the Binongko and Batu Hillareas, the conflict took place as people did not set any financial return.Keywords: land acquisitions of Komodo airport, conflict, compensation